2010
DOI: 10.1124/dmd.110.033233
|View full text |Cite
|
Sign up to set email alerts
|

TheN-Oxide Metabolite Contributes to Bladder Selectivity Resulting from Oral Propiverine: Muscarinic Receptor Binding and Pharmacokinetics

Abstract: ABSTRACT:We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
(35 reference statements)
1
17
0
1
Order By: Relevance
“…Moreover, peroxisomal catalase also accumulated in the cytosol and nuclei of propiverine-treated rats concurrently with DAAO. Taken together, our study indicates that Propiverine-N-oxide was also found to be the major metabolite formed in rats when administered orally, thus suggesting a similar pharmacological handling in humans and rats (Yamada et al 2010). In order to attain drug approval for propiverine in Japan and later in the EU, preclinical testing was carried out in mice, rats and dogs (Inoue et al 1989;Kohda et al 1989;Nakano et al 1989;Yamashita et al 1989Yamashita et al , 1990.…”
Section: Introductionmentioning
confidence: 57%
“…Moreover, peroxisomal catalase also accumulated in the cytosol and nuclei of propiverine-treated rats concurrently with DAAO. Taken together, our study indicates that Propiverine-N-oxide was also found to be the major metabolite formed in rats when administered orally, thus suggesting a similar pharmacological handling in humans and rats (Yamada et al 2010). In order to attain drug approval for propiverine in Japan and later in the EU, preclinical testing was carried out in mice, rats and dogs (Inoue et al 1989;Kohda et al 1989;Nakano et al 1989;Yamashita et al 1989Yamashita et al , 1990.…”
Section: Introductionmentioning
confidence: 57%
“…Further, the urine concentration of nicotine was about 4-fold higher than the plasma concentration (Onoue et al, in press). Recently, we revealed that urothelial muscarinic receptors were significantly affected by antimuscarinic agents excreted in the urine directly from the bladder luminal side as well as the circulating bloods (Yamada et al, 2010(Yamada et al, , 2011. Thus, the high concentration of nicotine excreted into urine likely contributed to the selective increase in bladder muscarinic receptors.…”
Section: Discussionmentioning
confidence: 97%
“…They should also take into account that propiverine and its various metabolites differ in their in vivo plasma concentrations [23]. For each of them, the relative contribution of the three molecular targets may differ in the generation of bladder selectivity and the overall relaxing effect in the lower urinary tract [24]. Even if propiverine itself turns out to have too little α 1 -antagonism in vivo, it is an exciting starting point for the future synthesis of balanced α 1 /muscarinic receptor antagonists.…”
Section: Discussionmentioning
confidence: 99%